A new family of conjugate gradient coefficient with application - Shapiee, Norrlaili; Rivaie, Mohd; Mamat, Mustafa; Liza Ghazali, Puspa (International Journal of Engineering and Technology, 2018)
Conjugate gradient (CG) methods are famous for their utilization in solving unconstrained optimization problems, particularly for large scale problems and have become more intriguing such as in engineering field. In this paper, we propose a new family of CG coefficient and apply in regression analysis. The global convergence is established by using exact and inexact line search. Numerical results are presented based on the number of iterations and CPU time. The findings show that our method is more efficient in comparison to some of the previous CG methods for a given standard test problems and successfully solve the real life problem.Â Â